Effect of collateral circulation in patients with multiple craniocervical artery stenoses - Ya Gao; Xuan Liu; Beibei Xu; Ximeng Zhang; Yiqing Wang; Jianqiang Ni; Yi Yang (Wiley, 2023)
Abstract Based on previous findings, collateral circulation in the brain is vital in mitigating cerebral ischemia's effects and influencing stroke risk. This retrospective study examined collateral circulation, admission ischemic stroke status, and long‐term recurrence in patients with multiple craniocervical artery stenoses. Consecutive symptomatic internal carotid artery (ICA) stenosis patients from the First Affiliated Hospital of Soochow University were recruited. Baseline data including medical histories and neurological function at admission were collected. Imaging techniques assessed collateral compensative capacity. Multivariate logistic regression analysis was used to investigate the association between collateral circulation and case status. A total of 559 patients with symptomatic ICA stenosis were included, among whom 153 (27.4%) had concurrent moderate to severe vertebro‐basilar artery (VBA) stenosis. Dizziness, weakness/numbness, and slurring of speech were the primary symptoms in all patients. Over 36 months, 71 (12.7%) patients experienced a recurrence of acute ischemic stroke (AIS). In multivariate analysis, collateral circulation was found to be negatively associated with AIS (regional leptomeningeal collateral [rLMC] scores: OR: 0.798, 95% CI: 0.743-0.857, p < 0.001; Tan scores: OR: 0.478, 95% CI: 0.336-0.679, p < 0.001). Meanwhile, the collateral circulation scores were significantly associated with the recurrence of AIS within 3 years (rLMC scores: OR: 0.926, 95% CI: 0.860-0.997, p = 0.042; Tan scores: OR: 0.467, 95% CI: 0.306-0.712, p < 0.001). Most associations remained significant in the subgroup of patients with VBA stenosis. Favorable collateral circulation in multiple craniocervical artery stenosis patients reduced long‐term ischemic event recurrence. Stratifying treatment risks is essential for optimizing outcomes.